The GAMBARAN EFEKTIVITAS ANTISEPTIK TERHADAP PERTUMBUHAN Candida albicans - Ndara Milla, Paul Hazler (Akademi Kesehatan John Paul II Pekanbaru, 2023)
Antiseptics are antimicrobial substances that aim to inhibit or damage microorganisms on the surface of a living tissue. Candida albicans is the cause of candidiasis. This antiseptic has a role as an antimicrobial. The purpose of the study was to determine how minimal antiseptic concentrations inhibit the growth of Candida albicans and to determine how much antiseptic concentration kills the growth of Candida albicans. Type of experimental research using antiseptic samples. Solid dilution method Pour cup technique. The results of the study on antiseptic A concentrations of 20% (140 x 102 Cfu/ml), 40% (40.5 x 102 Cfu/ml), 60% (38 x 102 Cfu/ml), 80% (0 colonies), 100% (0 colonies). At antiseptic B concentration 20% (144.5 x 102 Cfu/ml), 40% (52 x 102 Cfu/ml), 60% (38 x 102 Cfu/ml), 80% (0 colonies), 100% (0 colonies). At antiseptic C concentration 20% (145.5 x 102 Cfu/ml), 40% (22 x 102 Cfu/ml), 60% (20 x 102 Cfu/ml), 80% (0 colonies), 100% (0 colonies). The conclusion of this study is a decrease in the number of Candida albicans colonies in antiseptic A concentration of 60% (38 x 102 Cfu/ml) antiseptic B concentration of 60% (38 x 102 Cfu/ml), antiseptic C concentration of 60% (20 x 102 Cfu/ml). Concentrations where there is no growth of Candida albicans colonies are found in antiseptic A, B and C concentrations of 80% (0 colonies).